Atonal homolog 7 (ATOH7) loss-of-function mutations in predominant bilateral optic nerve hypoplasia. (7th November 2019) - Atac, David; Koller, Samuel; Hanson, James V M; Feil, Silke; Tiwari, Amit; Bahr, Angela; Baehr, Luzy; Magyar, István; Kottke, Raimund; Gerth-Kahlert, Christina; Berger, Wolfgang
Abstract: Optic nerve hypoplasia (ONH) is a congenital optic nerve abnormality caused by underdevelopment of retinal ganglion cells (RGCs). Despite being a rare disease, ONH is the most common optic disk anomaly in ophthalmological practice. So far, mutations in several genes have been identified as causative; however, many cases of ONH remain without a molecular explanation. The early transcription factor atonal basic-helix-loop-helix (bHLH) transcription factor 7 ( ATOH7 ) is expressed in retinal progenitor cells and has a crucial role in RGC development. Previous studies have identified several mutations in the ATOH7 locus in cases of eye developmental diseases such as non-syndromic congenital retinal non-attachment and persistent hyperplasia of the primary vitreous. Here we present two siblings with a phenotype predominated by bilateral ONH, with additional features of foveal hypoplasia and distinct vascular abnormalities, where whole-exome sequencing identified two compound heterozygous missense mutations affecting a conserved amino acid residue within the bHLH domain of ATOH7 (NM_145178.3:c.175G>A; p.(Ala59Thr) and c.176C>T; p.(Ala59Val)). ATOH7 expression constructs with patient single nucleotide variants were cloned for functional characterization. Protein analyses revealed decreased protein amounts and significantly enhanced degradation in the presence of E47, a putative bHLH dimerization partner. Protein interaction assays revealed decreased heterodimerization and DNA-binding of ATOH7 variants, resulting in total loss of transcriptional activation of luciferase reporter gene expression. These findings strongly support pathogenicity of the two ATOH7 mutations, one of which is novel. Additionally, this report highlights the possible impact of altered ATOH7 dimerization on protein stability and function.